Facial Emotion and Identity Processing Development in 5- to 15-Year-Old Children - Johnston, Patrick; Kaufman, Jordy; Bajic, Julie; Sercombe, Alicia; Michie, Patricia; Karayanidis, Frini (Frontiers in Psychology, 2011)
Most developmental studies of emotional face processing to date have focussed on infants and very young children. Additionally, studies that examine emotional face processing in older children do not distinguish development in emotion and identity face processing from more generic age-related cognitive improvement. In this study, we developed a paradigm that measures processing of facial expression in comparison to facial identity and complex visual stimuli. The three matching tasks were developed (i.e., facial emotion matching, facial identity matching and butterfly wing matching) to include stimuli of similar level of discriminability and to be equated for task difficulty in earlier samples of young adults. Ninety two children aged 5 to 15 years and a new group of 24 young adults completed these three matching tasks. Young children were highly adept at the butterfly wing task relative to their performance on both face-related tasks. More importantly, in older children, development of facial emotion discrimination ability lagged behind that of facial identity discrimination.